Valkyrie : the women of the Viking world - Friðriksdóttir, Jóhanna Katrín (London : Bloomsbury Academic, 2020)
Valkyries: the female supernatural beings that choose who dies and who lives on the battlefield. They protect some, but guide spears, arrows and sword blades into the bodies of others. Viking myths about valkyries attempt to elevate the banality of war – to make the pain and suffering, the lost limbs and deformities, the piles of lifeless bodies of young men, glorious and worthwhile. Rather than their death being futile, it is their destiny and good fortune, determined by divine beings. The women in these stories take full part in the power struggles and upheavals in their communities, for better or worse. Drawing on the latest historical and archaeological evidence, Valkyrie introduces readers to the dramatic and fascinating texts recorded in medieval Iceland, a culture able to imagine women in all kinds of roles carrying power, not just in this world, but pulling the strings in the other-world, too. In the process, this fascinating book uncovers the reality behind the myths and legends to reveal the dynamic, diverse lives of Viking women. --
Introduction : 'Valkyries decide who dies or lives' -- Infancy and childhood -- Teenage girls -- Adulthood, married life and divorce -- Pregnancy, childbirth and motherhood -- Widows -- Old age and death -- Epilogue.
Sisältää bibliografisia viitteitä ja hakemiston.
Julkaistu myös verkkoaineistona.
Hc2020A
Keywords: yliluonnolliset olennot; skandinaavinen mytologia; viikingit; naiset; övernaturliga väsen; nordisk mytologi; vikingar; kvinnor; Islanti; Island